Rehabilitation among individuals with traumatic brain injury who intersect with the criminal justice system: A scoping review - Chan, Vincy; Estrella, Maria Jennifer; Syed, Shazray; Lopez, Allison; Shah, Riya; Colclough, Zoe; Babineau, Jessica; Beaulieu-Dearman, Zacharie; Colantonio, Angela (Frontiers in Neurology, 2023)
Traumatic brain injury (TBI), a leading cause of morbidity and mortality globally, is highly prevalent among individuals who intersect with the criminal justice system (CJS). It is well-established that TBI negatively impacts individuals' interactions both within the CJS and upon release and is associated with serious disciplinary charges and higher recidivism rates. Although rehabilitation is fundamental to TBI recovery, it is not known to what extent rehabilitation is available to, or used by, individuals who intersect with the CJS. This scoping review explores the availability and extent of rehabilitation for individuals with TBI who intersect with the CJS, based on available literature. A systematic search of electronic databases (MEDLINE, Embase, Cochrane CENTRAL Register of Clinical Trials, CINAHL, APA PsycINFO, Applied Social Sciences Index and Abstracts, and Proquest Nursing and Allied Health), relevant organizations' websites, and reference lists of eligible articles identified 22 peer-reviewed articles and 2 gray literature reports that met predetermined eligibility criteria. Extracted data were synthesized through a descriptive numerical summary and qualitative content analysis. This review provides evidence that existing rehabilitation interventions are already serving individuals with TBI with a history of CJS involvement; however, they rarely consider or acknowledge TBI or CJS in their interventions. Findings also suggest opportunities to integrate rehabilitation for individuals with TBI who intersect with the CJS through TBI screening, education on TBI within CJS settings, and linkages to the community to facilitate continuity of care. This review also highlights significant gaps in knowledge regarding sex, gender, and other intersecting factors. Research to understand how these experiences impact the rehabilitation process throughout the CJS is urgently needed to enable timely and appropriate rehabilitation and continuity of care for diverse individuals with TBI who intersect with the CJS.